1990
DOI: 10.3382/ps.0691147
|View full text |Cite
|
Sign up to set email alerts
|

Nutrient Composition and Metabolizable Energy Values of Selected Grain Sorghum Varieties and Yellow Corn ,

Abstract: Three low-tannin sorghum grains and one high-tannin variety were grown at the same location in 1985,1986,1987, and 1988. The relative CP content of the grains varied among the years. The proteins of sorghum grain contained, on the average, higher concentrations of Ala, Asp, Glu, Leu, lie, Phe, Tyr, and Val; and lower concentrations of Arg, Gly, and His than did the protein of yellow corn. Both contained similar concentrations of Ser, Lys, Met, Cys, and Thr. An increase in the CP of sorghum grain did not result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
14
2
2

Year Published

1992
1992
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(26 citation statements)
references
References 14 publications
3
14
2
2
Order By: Relevance
“…The ADF and NDF contents in sorghum and regular corns are in agreement with the average values reported by CVB (1998), but higher than those reported by NRC (1998). Douglas et al (1989) reported that the ADF content among four different sources of corn varied from 49 to 89 g kg -1 and NDF from 90 to 190 g kg -1 . Yin et al (1993) reported that the NDF content of two different varieties of corn varied from 186 to 256 g kg -1 and ADF content from 8 to 15 g kg -1 .…”
Section: Resultsmentioning
confidence: 99%
“…The ADF and NDF contents in sorghum and regular corns are in agreement with the average values reported by CVB (1998), but higher than those reported by NRC (1998). Douglas et al (1989) reported that the ADF content among four different sources of corn varied from 49 to 89 g kg -1 and NDF from 90 to 190 g kg -1 . Yin et al (1993) reported that the NDF content of two different varieties of corn varied from 186 to 256 g kg -1 and ADF content from 8 to 15 g kg -1 .…”
Section: Resultsmentioning
confidence: 99%
“…proanthocyanidins, PA) in poultry feeds has been shown to have negative effects on live performance of broiler chicks (Armstrong et al, 1974;Sell et al, 1985;Rubio et al, 1990). These negative effects have been shown such as reduced body weight gain and feed efficiency (Douglas et al, 1990;Elkin et al, 1990) and has been attributed to the ability of tannins to bind, coagulate and precipitate protein (Butler et al, 1986) including digestive enzymes through hydrophobic and other interactions (Hagerman et al, 1981), thereby reducing digestion and absorption of nutrients (Farrell et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…Douglas et al (1990) afirmam que houve decréscimos lineares da energia digestível e energia metabolizável, à medida que o teor de tanino aumentou no grão de sorgo. Porém, outros estudos não relatam efeito sobre o ganho de peso quando o sorgo foi utilizado na ração (MUSHARAF & LATSHAW, 1991).…”
Section: Introductionunclassified